KUALITAS PELAYANAN TIKET DI PT. OKE WISATA TOUR AND TRAVEL - Suriati "; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Is in the interval 2,8-3,6. PT. Oke Wisata Tour and Travel Tourism needs to maintain the elements that have been considered good by customers as well as the need to fix the things that are still considered less.quality of service, openness (openness), positiveness (reliability), supportiveness (responsiveness), equality (assurance), empathy (caring), this study aims to determine the dimensions or indicators of service quality, namely openness (openness) , positiveness (reliability), supportiveness (responsiveness), equality (security) and empathy (caring), PT. Oke Wisata Tour and Travel Tourism and determine the most dominant factors that affect customer satisfaction PT. Oke Wisata Tour and Travel. The population in this study is the customers who come to PT. Oke Wisata Tour and Travel. Samples were taken by 30 respondents using the technique of Non-Probability Sampling with Accidental sampling approach, which is based on accidental sampling technique, namely, who happened to meet with researchers can be sampled as it sees fit. Based on the translation of each indicator, the most dominant factor affecting the quality of service in the PT. Oke Wisata Tour and Travel is supportiveness. It can be seen from the statement of the respondents in all the indicators, and supportiveness obtain the highest average value of 3,49. Value of 3.49 is included in the Good Enough category, is seen from the overall average results of respondents' statements.Key Words: PT. Oke Wisata Tour and Travel’s ticket service quality